The Effectiveness Of Health Education On Personal Hygiene In Improving Knowledge And Attitudes Toward The Prevention Of Scabies Among Students At Assa'idiyyah Islamic Boarding School In Kediri City - Ilmia Larashati; Reny Maretasari (Universitas STRADA Indonesia, 2026)
Scabies is a contagious skin disease caused by Sarcoptes scabiei var. hominis . This condition represents a significant health problem as it can lead to severe morbidity and, if left untreated, may even result in mortality. The high prevalence of scabies in Islamic boarding schools is influenced by the lack of knowledge and attitudes among students regarding personal hygiene. This study aims to determine the effectiveness of health education on personal hygiene in improving knowledge and attitudes toward the prevention of scabies among students. This research employed a pre-experimental design with a one-group pre-post test approach. A total of 63 respondents were selected using stratified random sampling. The results showed that prior to the health education intervention, 92.2% of respondents had poor knowledge and 85.7% had poor attitudes. After the intervention, good knowledge increased to 44.1% and good attitudes increased to 48.9%. Data analysis using the Wilcoxon Sign Rank Test revealed a p-value of 0.000 (<0.05), indicating a significant difference in students' knowledge and attitudes before and after the intervention. The implementation of health education proved effective in enhancing students' knowledge and attitudes regarding personal hygiene and can serve as an important source of information in the prevention of scabies in Islamic boarding schools.